2015
DOI: 10.3389/fgene.2015.00185
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of C19orf12, coding for a transmembrane glycine zipper containing mitochondrial protein, cause mis-localization of the protein, inability to respond to oxidative stress and increased mitochondrial Ca2+

Abstract: Mutations in C19orf12 have been identified in patients affected by Neurodegeneration with Brain Iron Accumulation (NBIA), a clinical entity characterized by iron accumulation in the basal ganglia. By using western blot analysis with specific antibody and confocal studies, we showed that wild-type C19orf12 protein was not exclusively present in mitochondria, but also in the Endoplasmic Reticulum (ER) and MAM (Mitochondria Associated Membrane), while mutant C19orf12 variants presented a different localization. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 46 publications
(66 reference statements)
5
73
1
Order By: Relevance
“…In addition, overexpression of wild‐type C19orf12 increased lipidated LC3 and reduced the amount of the autophagy substrate p62. However, overexpression of mislocalized mutants failed to promote autophagy and levels of basal autophagy remained unchanged during exposure to oxidative stress in HeLa cells …”
Section: Mitochondrial Membrane Protein‐associated Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, overexpression of wild‐type C19orf12 increased lipidated LC3 and reduced the amount of the autophagy substrate p62. However, overexpression of mislocalized mutants failed to promote autophagy and levels of basal autophagy remained unchanged during exposure to oxidative stress in HeLa cells …”
Section: Mitochondrial Membrane Protein‐associated Neurodegenerationmentioning
confidence: 99%
“…Mitochondrial membrane protein‐associated neurodegeneration, also called hereditary spastic paraplegia type 43 (SPG43), is the third most common disease belonging to neurodegeneration with brain iron accumulation disorders. Patients with mitochondrial membrane protein‐associated neurodegeneration often suffer from cognitive decline, in addition to dystonia, gait and speech disturbance, or Parkinsonism . Age at onset is highly variable, but most patients present in childhood to early adulthood with slow progression .…”
Section: Mitochondrial Membrane Protein‐associated Neurodegenerationmentioning
confidence: 99%
“…The protein has been localized to mitochondria, endoplasmic reticula, and mitochondrial-associated membranes, and its long hydrophobic domain and glycine zipper motifs suggest that it may be a transmembrane protein (Venco et al, 2015). Mutations in C19orf12 result in a higher percentage of the protein outside the mitochondria perhaps due to inability to fit into membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Its physiological function and the mechanism of iron accumulation located into GP and SN are not entirely understood [82]. A case study reported no change in clinical status after chelation therapy with 30 mg/kg/day deferiprone lasting two years [83].…”
Section: Other Nbia Disordersmentioning
confidence: 99%